Enhancing the efficacy of synthesising PHA from nitrogen-limited activated sludge using magnetic field - Guo, Xiaomin (Environmental technology, 2025)
Polyhydroxyalkanes (PHA) is a biodegradable biopolyester. In this study, we introduced the biological effects of magnetic field into a sequencing batch reactor (SBR) for PHA production to evaluate the effect of different strength of magnetic field on the efficacy of PHA synthesis by activated sludge and used the magnetic field to enhance the PHA synthesis capacity of nitrogen-limited activated sludge and to optimise the percentage of the content of the two monomers in PHA. The results showed that the magnetic field of appropriate strength was favourable to increase the production of PHA and to increase the percentage of PHV. In addition, microbial community analysis showed that there was an obvious succession of key functional bacteria under different strength of magnetic field. The highest PHA accumulation was achieved after the magnetic field of 16 mT, which reached 57.65% of the dry weight of sludge. In addition, the PHV monomers were more sensitive to the response of the magnetic field, and the magnetic field of 8mT and 16mT positively promoted the synthesis of PHV. It is worth noting that too high a magnetic field would have an inhibitory effect on the synthesis of PHA